Integrating Technology in EFL Classrooms for Vocabulary Acquisition - Noveriana Chang, Afnesha (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This study explores the integration of technology in English as a Foreign Language (EFL) classrooms to enhance vocabulary acquisition. Drawing upon a literature review of empirical studies, it examines the effectiveness of various technological tools and approaches, including mobile-assisted vocabulary learning (MAVL) with spaced repetition systems, gamification for motivation, augmented reality (AR) for contextual learning, learner-created multimedia for active processing, and a pedagogical integration framework for cohesive instructional design. Findings indicate that while each technology offers unique benefits such as improved retention, increased learner autonomy, and contextual depththeir effectiveness depends on strategic pedagogical implementation. The synthesis of results suggests that combining MAVL for individual study, gamification for sustained engagement, AR for immersive contextualization, and multimedia production for output-focused tasks can create a multimodal, learner-centered vocabulary learning ecosystem. This integrative approach aligns with cognitive and sociocultural theories of language learning, offering a comprehensive model for technology-enhanced EFL vocabulary instruction.